Comparative studies between herbal toothpaste (dantkanti) and non-herbal tooth paste - Singh, Kuldeep; Singh, Pooja; Oberoi, Gurpreet (International Journal of Dental Research, 2016)
The purpose of the paper is to highlight the advantages of using the herbal tooth paste with that of conventional paste. The approach is to make use of naturally available herbs such as Akarkara (anacyclus pyrethrum), Neem (azadirachta indica), Babool (acacia arabica), Haldi (curcuma longa) etc to make herbal paste. These herbal mixture acts as antimicrobial agents. The clinical study is carried out with three parameters – Debris index, Calculus index and Gingival bleeding index. These parameters were compared over conventional paste. We have carried out studies with 100 people of different age groups ranging from 25 to 50 years covering both men and women. The statistical t-test is carried out between the unpaired two groups of herbal and non-herbal pastes. The results shows that the group – A (herbal) has significantly lower debris, calculus and gingival bleeding index value. The debris index and calculus index have p < 0.001, the oral hygiene index also has the p < 0.001, which is significant and the gingival bleeding index has the p < 0.05.The conclusion is that the herbal Dantkanti toothpaste is more efficient in maintenance of oral hygiene and gum bleeding as compared to the non-herbal toothpaste.